Application of wavelet theory to identify yielding in seismic response of bi-linear structures. - Pan, Tso-Chien (Earthquake engineering & structural dynamics.)
The time frequency and the time scale analysis methods are used in this paper to identify the dynamic characteristics of non-linear seismic response of structural systems with single degree of freedom (SDOF) and multiple degrees of freedom (MDOF). Based on the floor acceleration response time histories of bi-linear SDOF and MDOF structures, the current study compares the results of system identification using the short time Fourier transform (STFT), continuous wavelet transform (CWT) and discrete wavelet transform (DWT) methods. The aim is to identify the frequency variations and the time at on-set of yielding and unloading of a bi-linear structural system during seismic response. The results demonstrate that the CWT method is better than the STFT method in both time and frequency resolutions, and that the DWT method is the best at detecting the time at on set of yielding and unloading. Combining the results of CWT and DWT methods therefore provides accurate information of both frequency variations and yielding time in non linear seismic response. To alleviate the problems associated with noise contaminated signals, e.g. seismic response data recorded on site, the study suggests that low pass filtering be carried out before applying the DWT method to decompose the signals into multiple levels of details.